Pemberdayaan Masyarakat Melalui Pengolahan Pepaya Menjadi Manisan Kering Untuk Meningkatkan Nilai Tambah Kemandirian Pangan Lokal,dan UMKM - Nabila Tri Amanda; Gitta Destalya Adrian Nova; Lara Novalia; Haris Haris; Anjelia Putri (Jurnal Inovasi Pengabdian Masyarakat, 2026)
Battu Winangun Village is one of the villages with abundant agricultural resource potential, especially papaya plants. However, the utilization of papaya fruit has so far been very limited to fresh consumption and does not yet have optimal economic value-added for the community. This community service activity aims to empower the people of Batuwinangun Village through innovation in managing papaya into processed products in the form of dried candied fruit which has a long shelf life and high selling value. The methods used include field observation, socialization of local food potential, technical processing training, production assistance, and activity evaluation. The results of the service show a significant increase in public knowledge and skills in processing papaya into innovative food products. This dried papaya candy innovation is expected to become a regional superior product capable of supporting food independence while strengthening the sustainable development of village MSMEs.